EFEKTIFITAS PEMBERIAN NUTRISI ENTERAL METODE INTERMITTENT FEEDING DAN GRAVITY DRIP TERHADAP VOLUME RESIDU LAMBUNG PADA PASIEN KRITIS DI RUANG ICU RSUD KEBUMEN - Wisnu Munawaroh, Sri; -, Handoyo; Astutiningrum, Diah (LPPM STIKES MUHAMMADIYAH GOMBONG, 2012)
Intermittent feeding method is enteral nutrition support that using electrical pump. Meanwhile, gravity drip method is enteral nutrition support using gravitation. Currently, there are two methods used in giving nutrition to the patients who are admitted at intensive care unit. However, currently there are no studies performed to evaluate the effectiveness of both feeding methods for critical patients who are admitted at hospital. The objective of the research was to find out effectiveness of enteral nutrition support by intermittent feeding and gravity drip methods to gastric residuals volume in critical patients. The design use in the research was a Quasi Experimental design, with post test only control group design. The samples were 60 subjects and divided into two groups. Respondents were taken by accidental sampling method. From the result of statistical independent t-test, show that there are mean value at intermittent feeding method amount of 2,46 ml and Mean value at gravity drip method amount of 6,93 ml, t = -2,073 and p = 0,045. Based on statistical analysis show that there were significant differences of giving nutrition to critical patients by intermittent feedingÂ andÂ gravity drip methods. Intermittent feeding method more effective than gravity method in giving nutritional support for critical patients at RSUD Kebumen Keywords : intermittent feeding, gravity drip, gastric residuals volume, critical patients